Comparing the Effectiveness of Emotion Socialization and Parenting Metaphors Training for Mothers on Feeling of Shame in children with Internalized Behavioral Problems - Shahrzad Doustani; Amir Ghamarani (پژوهش‌های علوم شناختی و رفتاری, 2021)
Behavioral problems affect one's adaptive functioning in the practical, social, and conceptual domains. One of the most important family factors in the development of behavioral problems is parenting styles. The purpose of this study was to compare the effectiveness of emotion socialization and parenting metaphors training on Feeling of Shame in children with internalized behavioral problems. The research method was experimental with a pre-test post-test design with a control group. First, the subjects screened according to the inclusion criteria, then 45 mothers with children with internalized behavioral problems were selected and randomly assigned to three groups of 15 (two experimental and one control group). Mothers were trained in the Emotional Socialization Group for eight sessions, and in the parenting metaphors group for seven sessions. The control group received no intervention. The research tools included Achenbach Behavioral Problems Questionnaire (Parent Form) and TOSCA_C Shame and Guilt Questionnaire. Data analysis using covariance analysis showed that both trainings significantly reduced Feeling of Shame, but emotion socialization training was better than parenting metaphor training in reducing the signs and symptoms of shame in Children with internalized behavioral problems. This difference might indicate the stronger impact of emotion-centered parenting styles on Feeling of Shame compare to the cognitive methods because techniques such as identifying the causes and consequences of emotions and emotion-centered dialogue is closely related to the internalized behavioral problems.